Galileo multi-day precise orbit determination using L-band and SLR data - Tianhe Xu; Honglei Yang; Song Li; Zhenlong Fang; Wenfeng Nie; Min Li; Baoguo Yu (Geodesy and Geodynamics)
The continuously available satellites of European Galileo currently reach more than 25. To explore the rationality and reliability of the L-band and satellite laser ranging (SLR) data processing strategies, we design the Galileo L-band, the SLR-only, and the combined L-band/SLR dynamic precise orbit determination (POD) strategies by using the normal equations (NEQs) stacking, and investigate their continuity and stability by employing the Galileo L-band data and SLR observations for the time span of the whole year of 2023, based on the BeiDou/GNSS analysis center platform of Shandong University by using the modified Bernese GNSS Software Version 5.4. The orbital consistency of the L-band 1-day solution is the best with the Three-dimensional Root-Mean-Square (3D-RMS) values of 3.6 cm compared with the Center for Orbit Determination in Europe Multi-GNSS Experiment (COM) orbits, the corresponding values is 1.4 cm, 2.5 cm, and 2.3 cm in Radial, the Tangential, and the Normal (RTN) direction, respectively. While the SLR-only 9-day arc length is optimal with the RTN values of 5.3 cm, 30 cm, and 38.2 cm, as well as the 3D-RMS values of 48.9 cm. Encouragingly, the difference of the orbital accuracy between the combined L-band/SLR multi-day solution and the COM orbits is reduced by 0.5 cm and 0.9 cm, 0.6 cm and 1.2 cm in T-, and N-direction for the 3- and 5-day solution respectively. The corresponding values improve 0.7 cm and 0.9 cm, 1.4 cm and 1.8 cm for the 3- and 5-day orbital overlaps difference between the combined L-band/SLR and the L-band solution. Take the E09 satellite as a case study, the SLR-only orbital accuracy is regularly optimized as the multi-day arc lengthens and with the sites increase. Furthermore, the SLR residuals of its three types of orbits further demonstrate the positive contribution of SLR to the combination of the GNSS and SLR techniques.